Fabrication and Characterization of Chitosan-Collagen Membrane from Barramundi (Lates Calcarifer) Scales for Guided Tissue Regeneration - Susanto, Agus; Satari, Mieke Hemiawati; Abbas, Basril; Koesoemowidodo, R. Setyo Adji; Cahyanto, Arief (European Journal of Dentistry, 2019)
Objectives The aim of this study was to evaluate the synthesis, mechanical strength, and morphology of chitosan–collagen membranes from barramundi scales for guided tissue regeneration technique.Materials and Methods Collagen was extracted from barramundi scales by immersion in acetic acid. The resulting wet collagen was later dried. The membrane was fabricated by mixing chitosan with collagen from barramundi scales. Membrane characterization parameters were measured using Fourier transform infrared (FTIR), scanning electron microscopy (SEM) and mechanical property.Results The FTIR spectrum showed the typical peak of the mixture of chitosan and collagen. The tensile strength and elongation at break of the membrane in dry condition were 0.28 MPa and 8.53%, respectively, while in the wet condition these were 0.12 MPa and 25.6%. The membrane porosity test result was 38.85%; SEM result showed a porous membrane surface with size varying around 16 to 100 µm.Conclusion The chitosan-collagen membrane from the barramundi scale showed the fibrous membrane surface that has ideal porous size as guided tissue regeneration membrane and the lower mechanical strength.
Keywords: characterization; chitosan; collagen; membrane; guided tissue regeneration